2008
DOI: 10.1063/1.3013451
|View full text |Cite
|
Sign up to set email alerts
|

Theory and simulation of lower-hybrid drift instability for current sheet with guide field

Abstract: The stability of a thin current sheet with a finite guide field is investigated in the weak guide-field limit by means of linear theory and simulation. The emphasis is placed on the lower-hybrid drift instability (LHDI) propagating along the current flow direction. Linear theory is compared against the two-dimensional linear simulation based on the gyrokinetic electron/fully kinetic ion code. LHDI is a flute mode characterized by k⋅Btotal=0; hence, it is stabilized by a finite guide field if one is confined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The LDHI has been suggested as a possible source of observed waves near the lower hybrid frequency in the vicinity magnetopause reconnection regions [e.g., Bale et al, 2002;Eastwood et al, 2009;Zhou et al, 2009]. However, in its simplest form, the LHDI [e.g., Davidson and Gladd, 1975;Davidson et al, 1977]; Yoon et al, 2008] is expected (1) to produce fluctuations at f lh , (2) to be electrostatic (longitudinal), (3) to have k || = 0, and (4) to draw its energy from an electron drift due to ∇P e . The LHDI has been extended to include waves below f lh [e.g., Bale et al, 2002] and/or have an electromagnetic component [Daughton, 2003].…”
Section: 1002/2016gl072493mentioning
confidence: 99%
See 1 more Smart Citation
“…The LDHI has been suggested as a possible source of observed waves near the lower hybrid frequency in the vicinity magnetopause reconnection regions [e.g., Bale et al, 2002;Eastwood et al, 2009;Zhou et al, 2009]. However, in its simplest form, the LHDI [e.g., Davidson and Gladd, 1975;Davidson et al, 1977]; Yoon et al, 2008] is expected (1) to produce fluctuations at f lh , (2) to be electrostatic (longitudinal), (3) to have k || = 0, and (4) to draw its energy from an electron drift due to ∇P e . The LHDI has been extended to include waves below f lh [e.g., Bale et al, 2002] and/or have an electromagnetic component [Daughton, 2003].…”
Section: 1002/2016gl072493mentioning
confidence: 99%
“…One possibility is a modified two‐stream instability [ McBride et al, ; Ji et al, , ] from the strong electron drift or from ion motion [ Wang et al, ]. The observed waves also have some characteristics of a lower hybrid drift instability (LHDI) [ Krall and Liewer , ; Yoon et al, ], which has been suggested to occur in the magnetopause region [ Bale et al, ; Daughton , ; Zhou et al, ; Pritchett et al, ]. However, the observed waves are not entirely consistent with the classic derivation of the LHDI, which we discuss later.…”
Section: Introductionmentioning
confidence: 99%
“…Similar growth rates were obtained in the theoretical and simulation study of lower hybrid drift instability in the current sheets of the magnetotail by Yoon et al . []. When the ion diamagnetic drift speed is much faster than the ion thermal speed, V di ≳ 5 V i , in the Harris current sheet with its half width a fraction of the ion gyroradius, L HCS ~ 0.23 ρ i , they have found that the maximum growth rate of lower hybrid waves, normalized by lower hybrid frequency, can exceed the unity, γ LH / ω LH > 1, without or with the presence of weak guide field, B guide < 0.1 | B |.…”
Section: Discussionmentioning
confidence: 99%
“…The latter plays an important role in magnetic reconnection since it validates the magnetohydrodynamic approximation as well as affects the onset and evolution of the reconnection process, the dynamic properties of the current sheet, as well as the occurrence of transient shocks, secondary instabilities, etc. [15][16][17][18][19][20][21][22] For this reason, the stability of current sheets with a finite guide field has received much attention. [17][18][19][20][21][22] In this paper, we consider the LHDI in a current sheet containing a finite guide field and energetic particles by solving the Vlasov-Maxwell system.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] For this reason, the stability of current sheets with a finite guide field has received much attention. [17][18][19][20][21][22] In this paper, we consider the LHDI in a current sheet containing a finite guide field and energetic particles by solving the Vlasov-Maxwell system. It is found that the growth rate and the electromagnetic component of the LH wave increase with the strength of guide field, which also destroys the symmetry properties of the modes.…”
Section: Introductionmentioning
confidence: 99%